Investigation of the cardiac electrophysiological effects of acetylcholine and pharmacological modulation of early repolarization syndrome on canine and human ventricular preparations - Magyar Tibor (2023)
Abstract Introduction: Parasympathetic nervous system has been reported to provide an antiarrhythmic effect during ischemia. On the other hand it might exert a proarrhythmic role in Early Repolarization Syndrome. The exact cardiac electrophysiological effects of muscarinic agonists in these conditions are not fully understood. Methods: Action potentials were registered utilizing the standard microelectrode technique from human donor cardiac preparations and canine papillary muscles (PM) and free-running Purkinje fibers (PF). Ionic currents were measured using the whole-cell configuration of the patch clamp method. Results: 5 μM acetylcholine alone did not alter the action potential duration (APD) either in canine Purkinje fibers (233.6 ± 4.7 ms vs 231.7 ± 4.6 ms, n=15) or in papillary muscle (172.6 ± 5.7 ms vs 172.8 ± 5.3 ms, n=5) preparations . In contrast, after proadministration of I KATP activator pinacidil (5 µM) (n=8) which caused a significant and large APD 90 reduction (from 207.7 ± 7 ms to 113.1 ± ms, p < 0.05), the cumulative addition of acetylcholine (5 µM) resulted in significant APD 90 lengthening as early as 3 minutes (from 113.1 ± ms to 147.3 ± 7.4 ms, p < 0.05) in Purkinje fibers. In papillary muscles, after pinacidil induced APD shortening (187.9 ± 4.5 ms vs 163.7 ± 6.4 ms, p < 0.05) acetylcholine (5 µM) was able to oppose incompletely the effect of pinacidil (from 163.7 ± 6.4 ms to 172.1 ± 7.4 ms, n=7, p < 0.05). The dispersion of control APD 90 (9.5%, 20 ms, n=8 PF, n=7 PM) was significantly increased by the administration of pinacidil (APD 90 dispersion: 44.7%, 51 ms, n=8 PF, n=7 PM). However, the cumulative addition of acetylcholine resulted in significant reduction of this dispersion (16.9%, 28 ms; n=8 PF, n=7 PM, p < 0.05). Carbachol alone did not change the control current (0 mV control: 0.20 ± 0.2 pA/pF vs 3 μM carbachol: 0.32 ± 0.2 pA/pF, n=6 and +30 mV - control: 0.55 ± 0.4 pA/pF vs 3 μM carbachol: 0.74 ± 0.3 pA/pF, n=6). In case of prior 5 μM pinacidil application, carbachol administration resulted a significant attenuation of the current at both voltages (0 mV – control: 0.24 ± 0.2 pA/pF  5 μM pinacidil: 2.03 ± 0.3 pA/pF  3 μM carbachol: 1.51 ± 0.4 pA/pF, n=8, p < 0.05. +30 mV - control: 0.78 ± 0.6 pA/pF  5μM pinacidil: 3.17 ± 0.3 pA/pF  3 μM carbachol: 2.26 ± 0.3 pA/pF, n=8, p < 0.05). Hypoxic condition resulted in shortening of APD 90 (181.4 ± 5.7 ms to 135.0 ± 8.6 ms) (n=5, p < 0.05), reduction of amplitude (103.7 ± 2.8 mV vs 92 ± 3.5 mV, n=5) and decrease of the maximum rate of depolarization (185.8 ± 15.8 V/s vs 156.1 ± 20.6 V/s, n=5). After 5 μM acetylcholine application significant APD 90 prolongation (from 135.0 ± 8.6 ms to 164.4 ± 4.4 ms) and AMP recovery to a normal range (102.1 ± 1.6 mV, n=5) were seen, while V max remained at the same value (156.0 ± 16.1 V/s, n=5). Acetylcholine (5 μM) exerted various electrophysiological effects in human donor cardiac preparations. Cilostazol partially reversed the effects of ionic channel modulators in Early Repolarization Syndrome models. Conclusions: 5 μM acetylcholine was able to partially antagonize the APD shortening caused by the previously used I KATP activator (5 µM pinacidil) and decreased the pinacidil induced APD dispersion elevation between ventricular papillary muscle and Purkinje fibre. 3 μM carbachol inhibited the ATP-sensitive K + current. After the generation of hypoxic environment, the use of acetylcholine was able to offset hypoxia-induced APD 90 shortening, and decrease in amplitude. Activation of the parasympathetic nervous system might reduce the arrhythmogenic substrate providing antiarrhythmic mechanisms during ischemic conditions. Cilostazol might be recommended for the treatment of some forms of Early Repolarization Syndrome.